Profil Sitotoksik ekstrak Lithocarpus bancanus dan Fraksinya Terhadap Lini Sel Kanker Paru-Paru A549 - Hilwan Yuda Teruna; Rudi Hendra; Retno Puji Lestari; Titania Tjandrawati Nugroho; Saryono Saryono; Jasril Jasril; Muhammad Almurdani; Rizky Abdulah (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2026)
Lithocarpus bancanus is a medicinal plant used by communities in Riau Province, Indonesia. This plant is a tree locally known in the province as mempening. In this study, the cytotoxic activity profiles of the methanolic extract, n-hexane fraction, dichloromethane fraction, and ethyl acetate fraction from L. bancanus leaves were evaluated against human lung cancer cells (A549 cell line) using the MTT assay. IC₅₀ values were calculated from dose–response curves analyzed using the 4-parameter logistic (4PL) model. The results showed IC₅₀ values of 455.1, 361.9, 132.9, and 304.7 µg/mL for the methanolic extract, n-hexane fraction, dichloromethane fraction, and ethyl acetate fraction, respectively, with the dichloromethane fraction exhibiting relatively higher cytotoxic activity (IC₅₀ = 132.9 µg/mL). Cisplatin was used as the positive control and showed an IC₅₀ of 103.9 µg/mL. Meanwhile, the methanolic extract as well as the n-hexane and ethyl acetate fractions showed low cytotoxic activity, with IC₅₀ values greater than 300 µg/mL. Therefore, the dichloromethane fraction can serve as a basis for further isolation to identify bioactive anticancer compounds.